IMPLEMENTASI PROGRAM KARTU ANAK JAKARTA (KAJ) DALAM UPAYA MENINGKATKAN KESEJAHTERAAN ANAK DI KELURAHAN GALUR KECAMATAN JOHAR BARU JAKARTA PUSAT - Ailsa Apta Faustina; Amni Zarkasyi Rahman (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2026)
The high prevalence of stunting in Galur Village, Johar Baru District, Central Jakarta, is one of the backgrounds for the presence of the Jakarta Child Card Program (KAJ) as a social assistance policy of the DKI Jakarta Provincial Government aimed at children aged 0-6 years from underprivileged families to meet basic needs and improve children's welfare. The problem of this study is the still high prevalence of stunting and the decrease in the number of KAJ recipients in Johar Baru District, especially in Galur Village, which is not comparable to the socio-economic conditions of the local community. This study aims to analyze the suitability of the implementation of the Jakarta Child Card Program, as well as identify the driving and inhibiting factors in its implementation towards improving child welfare. The methods used are a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation, as well as purposive informant selection and snowball sampling with validity tests through source triangulation. The results of the study show that the implementation of the program has been carried out according to procedures and provides benefits in helping to meet the nutritional and health needs of children, but it has not been appropriate due to policy shifts in the transition to data collection that are still in the process of improving features and the intimeliness of KAJ users in taking cards. In addition, factors were found that hindered the implementation of the KAJ program, namely uneven socialization constraints, and limited social assistance staff in Galur Village. The conclusion of this study emphasizes that the implementation of the Jakarta Children's Card Program contributes to children's welfare, but requires a more integrated data collection strategy, timely card collection, increased socialization, and an increase in the number of social assistance staff to be more sustainable.